Estudo sobre teletrabalho na percepção de quem o deseja - Larangeira, Gabriel Olivier Bragança (2022)
The topic addressed at this work is directly linked with the desire of the workers at the state of São Paulo referring to teleworking, which gain a lot of visibility at the last years manly at the pandemic period, which a lot of people where obligated to stay at home to protect themselves. With the change between, the presential model going to the teleworking, many difficulties emerged during the process, but today company´s already became stable with this model, looking more at the advantages that will be spoken during this work. The pandemic brings the teleworking with strength for the day by day at the company´s, that changes the role process and controls, in the past everything was stored ate file folders, and now they can easily be found at a server that can be accessed from every place. Through a questionnaire done anonymous, we can understand the preference by some people about their work model and your advantages and disadvantages, being such a young process, they have their opportunities and gaps, but is very important for many people. Can be observed after the last analyze that isn´t the most desire bust he is still part of the hybrid model, that makes him stronger, even the presential model still existing for so long